MODAL SOSIAL DALAM PENGELOLAAN BANK SAMPAH BUKIT HIJAU BERLIAN KECAMATAN TAMPAN KOTA PEKANBARU - Ella Buswijaya; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Increasing population growth has resulted in increasing volume of waste, especially in urban areas. Various problems arise from the accumulation of garbage which results in environmental pollution. One of the major breakthroughs in waste management in Indonesia is through the waste bank program. Social capital must be built by the Bukit Hijau Berlian Waste Bank to be accepted by the community. This study aims to find out how the process of waste management in the Bukit Hijau Berlian waste bank and also to find out the elements of social capital contained therein. The design of this study is descriptive qualitative using observation, interview, and documentation techniques. The results of this study are that the social elements built by the waste bank ofBukit Hijau Berlian are 3, namely networks, norms and trust. The network that was built by the garbage bank of the Bukit Hijau Berlian is by forming a unit waste bank and also a garbage collector as a buyer. Some of the norms that must be obeyed by customers are the pricing of different waste and also withdrawal of savings that can only be done at the latest 6 months. The most important element of social capital is the trust that built the Bukit Hijau Berlian Waste Bank. Even though the price at the waste bank is cheaper, the community still chooses to sell the garbage to collectors because the waste bank has a savings system and also education obtained from the waste bank. Every party involved must work together so that the waste management process becomes more effective. Norms must also be obeyed so that there is trust between the parties involved.Keywords: Social Capital, Waste Bank